DEVELOPING A LOCAL CULTURE-BASED BILINGUAL STORYBOOK FOR IMPLEMENTING INDEPENDENCE CURRICULUM - Adiwijaya, Pande Agus; Sumiati, Ni Kadek Ayusri; Wedayanthi, Luh Made Dwi (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2025)
This study aims to develop a bilingual storybook that inserts local culture in the story for young learners in grade 4 at the State Elementary School 1 Kawan. This research uses level one (1) research and development method from Sugiono (2019). The steps in developing this research are (1) Potential and problems, (2) Literature study and collecting information (3) Product design (4) Product validation, (5) Tested design. The instruments used in this research are observation questionnaire, interview questionnaire, and questionnaire. The observation questionnaire was used to observe the needs and problems at the research site, the interview questionnaire was used to ascertain the needs of teachers and students, the questionnaire was used to assess the product by experts. Based on the recapitulation of the assessment conducted by three experts, namely two from ITP Markandeya Bali Lecturers and one from the research site. Obtained a score of 4,6 from the first expert, 4,73 obtained from the second expert, and 4,6 obtained from the third expert. Then the average score is 4,67 with the excellent category. Based on the results of the validation, it is stated that the results of the development of illustrated storybooks that insert local culture for young students in class 4th of Elementary School 1 Kawan are suitable for use.